Effect of climatic elements and phenomena on water consumption and water rationing of cucumber crop in Tarmiyah district - Zarzour, Manaf Muhammad; Muhammad, Ahmed (Al-Adab Journal, 2021)
This research is considered one of the researches in the field of applied-agricultural climate, as it aims to (calculate the climatic water balance, water consumption and water ration for cucumber crop for open cultivation in Tarmiyah district) and to show the extent of the climate impact on the net water ration. The study showed a permanent water deficit during the growing season of the cucumber crop, due to the varying rates of rain in the growing season, as the Samarra station recorded the highest amount of water deficit amounting to (-1244.3) mm, while the Khalis station recorded the lowest water deficit in the growing season of about (-941.1) mm, The study also showed that the water rating of the cucumber crop exposed by the irrigation method varies temporally and spatially in the study area, depending on the difference in the influence of climatic elements. Pure the lowest amount was about (1049.3) mm, the length of the growing season.